2004
DOI: 10.1148/radiol.2332031796
|View full text |Cite
|
Sign up to set email alerts
|

Routine Chest Radiography in a Primary Care Setting

Abstract: Routine chest radiography has low diagnostic yield in asymptomatic primary care patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 29 publications
1
14
1
2
Order By: Relevance
“…Our findings were consistent with that obtained by Tigges et al [4] who evaluated the diagnostic yield of used, with the benefits over potential risks carefully considered. If the benefits are outweighed by potential risks then the procedure might as well be given a second thought.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings were consistent with that obtained by Tigges et al [4] who evaluated the diagnostic yield of used, with the benefits over potential risks carefully considered. If the benefits are outweighed by potential risks then the procedure might as well be given a second thought.…”
Section: Discussionsupporting
confidence: 93%
“…The false-positive rates in our study are markedly lower than the false-positive rates found with routine screening chest radiography in asymptomatic patients (93.3%) (13). An interesting subgroup of our study is the fraction of patients (34.6%; 366 of 1057) who did not undergo a follow-up chest CT examination within 1 year.…”
Section: Discussioncontrasting
confidence: 61%
“…In an African study covering several institutions over a period of 5 years, only 7% of pre-employment radiographs showed abnormalities [8]. Tigges et al [9] reported that a mere 1.17% (n = 15) chest radiographs showed major abnormalities. Fourteen of the 15 findings of major abnormalities (lung nodules, mass, atelectasis, and mediastinal lymphadenopathy) proved to be false-positives.…”
Section: Discussionmentioning
confidence: 99%